Homeostasis loss in VIP deficient mice is associated with altered regulatory T cells recruitment - Gallino, Lucila (2019)
In order to have a successful pregnancy, it is required a balance between proinflammatory and tolerogenic mediators. Since VIP (vasoactive intestinal peptide) is a master regulator associated with Tregs induction and recruitment, we aim to understand the relevance of VIP in normal pregnancy with focus on the Tregs.